FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA PENGETAHUAN SISWA TENTANG KESEHATAN REPRODUKSI DI SMK NEGERI 1 MUNTOK (Program Studi Ilmu Kesehatan STIKESÂ Abdi Nusa Pangkalpinang, 2021)
Reproductive health is a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity, in all matters relating to the reproductive system and to its functions and processes. Teens are expected to carry their reproductive function properly therefore he must recognize reproductive organs. These latter problems can cause other problems as well as early marriage, abortion and unwanted pregnancy. The purpose of this research is to find out the relationship between attitudes, teacher support, information sources, parental support, the role of peers, the role of health workes with the low knowledge of students reproductive health at SMK Negeri 1 Muntok. This research was conducted using cross sectional method. The population in this study were 421 respondents of class X and XI of SMK Negeri 1 Muntok with a sample of 89 respondents. The sampling technique used simple random technique. The results of the study show that the factors associated with the low knowledge of students about reproductive health in SMK Negeri 1 Muntok are attitudes (p=0,000 POR=12,396), teacher support (p=0,001 POR=4,740), sources of formation (p=0,033 POR=2,841, parental support (p=0,001 POR=5,250), the role of peers (p=0,000 POR=7,543), the role of health workers (p=0,012 POR=3,287). The most dominant variable is attitude (p=0,000 POR=12,396). Is recommended that schools collaborate with health agencies to provide counseling to adolescents about reproductive health, reproductive health and the benefits of keeping the impact if it does not maintain reproductive health. Counseling is done to increase knowledge about reproductive health.